Digital Storytelling for Cultural Resilience: Revitalizing the Can Macanan Kadduk Performance in Arjasa Tourism Village - Evio Tanti Nanita (CV. Austronesia Akademika, 2025)
Traditional performing arts in rural tourism destinations are increasingly threatened by declining participation, limited institutional support, and weak digital visibility, creating an urgent need for adaptive strategies that sustain cultural continuity in the digital era. This study examines how digital storytelling can enhance cultural resilience and empower local communities in revitalizing the Can-Macanan Kadduk performance, a centuries-old traditional art from Arjasa Tourism Village, East Java. The research aims to analyze the role of narrative-driven digital media in strengthening community participation, intergenerational knowledge transfer, and cultural identity. Employing a qualitative descriptive case study design, data were collected through in-depth interviews with cultural practitioners, Pokdarwis members, and local digital creators, supported by observations and content analysis of Instagram, TikTok, and YouTube. Findings reveal that digital storytelling increases cultural visibility, fosters cultural pride, improves collaboration between youth and elders, and transforms traditional performances into dynamic cultural narratives accessible to wider audiences. The study also shows that participatory digital practices encourage shared ownership of heritage, bridge gaps between tradition and modernity, and support community-driven governance of cultural tourism. These results demonstrate that digital storytelling functions not only as a communication tool but also as a mechanism of empowerment that strengthens cultural resilience by enabling communities to adapt, innovate, and sustain their intangible heritage. The study concludes that integrating digital literacy, collaborative governance, and creative content development is essential for ensuring the long-term sustainability of traditional performing arts within Indonesia’s evolving digital tourism landscape.